2015
DOI: 10.1111/imr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐species communication in the Mycobacterium tuberculosis‐infected macrophage

Abstract: Summary Much of the infection cycle of Mycobacterium tuberculosis (Mtb) is spent within its host cell, the macrophage. As a consequence of the chronic, enduring nature of the infection, this cell/cell interaction has become highly intimate, and the bacterium has evolved to detect, react to, and manipulate the evolving, immune-modulated phenotype of its host. In this review, we discuss the nature of the endosomal/lysosomal continuum, the characterization of the bacterium’s transcriptional responses during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 121 publications
(224 reference statements)
0
20
1
Order By: Relevance
“…In response to the capability of host cells to eliminate them, pathogenic mycobacteria have evolved mechanisms for the manipulation of the host immune response by secretion of virulence factors through specialized secretion systems (Baxt et al, 2013;Houben et al, 2013). The bacteria are able to prevent lysosomal fusion and acidification of phagosomal compartments (Armstrong and Hart, 1971;Tan and Russell, 2015). Although a fraction of Mtb within a host cell is kept inside phagosomes, another fraction is able to escape from the phagosomes into the cytoplasm (van der Wel et al, 2007;Simeone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the capability of host cells to eliminate them, pathogenic mycobacteria have evolved mechanisms for the manipulation of the host immune response by secretion of virulence factors through specialized secretion systems (Baxt et al, 2013;Houben et al, 2013). The bacteria are able to prevent lysosomal fusion and acidification of phagosomal compartments (Armstrong and Hart, 1971;Tan and Russell, 2015). Although a fraction of Mtb within a host cell is kept inside phagosomes, another fraction is able to escape from the phagosomes into the cytoplasm (van der Wel et al, 2007;Simeone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the central role of the macrophage as host and effector cell during M . tuberculosis infection [ 43 , 44 ], many studies have been centered in macrophage cell cultures. In terms of human-based systems, monocyte-derived macrophages are the most widely used culture.…”
Section: Human-based In Vitro Models In Tb Researchmentioning
confidence: 99%
“…Furthermore, Mtb is able to direct fatty acid metabolites toward pathways that prevent their toxic accumulation within the granuloma [ 11 ]. Cholesterol esters are typically produced by foamy macrophages; thus, their presence in granulomas is indicative of a degenerative process which may lead to cell death and contribute to the development of caseous necrosis [ 112 ]. Labeling of macrophage with proprionate, oleate, and stearate within lipid droplets prior to infection demonstrated that Mtb has access to and incorporates host fatty acids into its cell wall lipids [ 11 ].…”
Section: The Granuloma As An Interface For Metabolism and Immunitymentioning
confidence: 99%